Culture and capability: essays in behavioural economics - Walsh, J (2022)
How do mental models guide behaviour? Although a great deal of attention has been paid to mental models in psychology, relatively little is understood about how they inﬂuence incentivised decision-making or their relevance for policy. In this dissertation, I explore this question over the course of four papers. In the ﬁrst paper, I synthesize the literature on mental models and aim to situate it in standard decision theory. In paper two, I look at how people use mental models of social groups to determine strategies of action under incentivized conditions. In paper three, I look at how unemployed young people’s mental model of their agency within the world inﬂuences their decisions to search for work. In paper four, I look at how mental models of technology inﬂuence vaccine hesitancy.